SPECIFICITY OF Haemolysin AND Gyrase GENE MARKER FOR RAPID DETECTION OF VIBRIOSIS ON PENAEID SHRIMP - Ince Ayu Khairana Kadriah; Sukenda Sukenda; Munti Yuhana; Endang Susianingsih; Muharijadi Atmomarsono (Indonesian Aquaculture Journal, 2013)
Pathogenic Vibrio spp. have been implicated as being one of the major causes of the disease problems in penaeid shrimp culture. For many pathogens, the outcome of the interaction between host and bacterium is strongly affected by the bacterial population size. Efforts for rapid molecular detection is to isolate specific genes which was owned by the pathogenic luminescent Vibrio and used it as the marker molecular in the rapid diagnosis of the disease. Haemolysin and gyrase gene known as one of the specific genes possessed pathogenic bacteria including Vibrio. The objectives of this study were to determine the specificity of designed specific primer from local isolate. Specificity test was performed for haemolysin primer (IAVhF1 and IAVhR1), gyrase primer (IAGyrF1 and IAGyr2) and commercial detection kit. The specificity test comparing the PCR result of pathogenic Vibrio DNA template as positive control, and DNA template from non pathogenic luminescent Vibrio, as well as pathogenic non Vibrios. The result showed that at annealing temperature of 60°C, haemolysin primer was more specific in detecting pathogenic Vibrio for penaeid shrimp than that of gyrase primer and commercial detection kit.